2002
DOI: 10.1080/10400435.2002.10132051
|View full text |Cite
|
Sign up to set email alerts
|

Future AAC Technology Needs: Consumer Perspectives

Abstract: This article suggests the need for rethinking the role that consumer perspectives will play (and ought to play) in the design and development of future augmentative and alternative communication (AAC) technologies. After carefully defining what they mean by "AAC consumers," "consumer perspectives," and "AAC technologies," the authors consider the extent to which current research has illuminated our understanding of (1) how consumers view AAC technologies and (2) how consumers themselves would define future tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…Research and development are needed (a) to improve the technology available to individuals who use AAC; (b) to design communication systems with reduced operational demands (Light, 1997;Light & Drager, 2002); and (c) to develop technology that can meet the needs of multi-lingual persons. This research must be consumer driven (Blackstone, Williams, & Joyce, 2002), because consumers are the best informants. It is by their personal experiences that we can learn about what is lacking and identify features for future development.…”
Section: Directions For Future Researchmentioning
confidence: 99%
“…Research and development are needed (a) to improve the technology available to individuals who use AAC; (b) to design communication systems with reduced operational demands (Light, 1997;Light & Drager, 2002); and (c) to develop technology that can meet the needs of multi-lingual persons. This research must be consumer driven (Blackstone, Williams, & Joyce, 2002), because consumers are the best informants. It is by their personal experiences that we can learn about what is lacking and identify features for future development.…”
Section: Directions For Future Researchmentioning
confidence: 99%
“…With this method, adaptations are made to the technology to improve its ease of use during user trials. Having end users inform AT design is recommended [24], but since the user in this study was a student with CCN who would have found it difficult to articulate recommendations, the need for adaptations was identified by observing the student performing the programming tasks [25]. If the participant appeared to be having difficulty controlling the cursor or taking a long time to accomplish tasks then adaptations were made to the SGD page and programming software in an effort to improve the ease of use for the participant.…”
Section: Methodsmentioning
confidence: 99%
“…In the United States, changes in federal laws, including Section 504 of the Rehabilitation Act (1973) and the Americans with Disabilities Act (1990), have been described as ''enabling legislation'' and have been mandated to improve accessibility (Blackstone, Williams, & Joyce, 2002). In Europe, similar legislation, such as the e-Europe Action Plan (Emiliani & Stephanidis, 2005) and the Disability Discrimination Act in the United Kingdom (Abascal & Nicolle, 2005), have addressed similar issues of technological exclusion.…”
Section: Public Policy Makersmentioning
confidence: 98%